Bovine fetal wastage in Southwestern Nigeria: a survey of some abattoirs. (2009)
As a result of inadequate veterinary services and indiscriminate slaughter of animals inmost Nigerian abattoirs, pregnant animals are often slaughtered resulting in wastage of scarce protein made available to the people. To this end, an evaluation of the volume of pregnant cows slaughtered at some abattoirs in Southwestern Nigeria between 2005 and 2007 based on meat inspection records was carried out with a view to determining the level of fetal wastage in this part of the country. A total of 321,448 cows were slaughtered, out of which, 16,092 (5.01%) were pregnant. The fetal wastages across the four seasons of the study period were statistically significant (P<0.05); the late dry season showing the highest percentage. There was a downward trend across the years, and this was considerably lower in 2007 than the other 2 years which were not statistically different from each other (XA2005=224.33; XA2006=216.38; XB2007=126.38). Our results indicated a considerable level of slaughtering of pregnant cows in the abattoirs studied. Hence, we advocate stepping up routine veterinary checks and interventions among trade animals in order to salvage the high level of fetal wastage in the region and the country at large.